Population Growth and Chlorophyll Content of Spirulina platensis Fertilized with Azolla microphylla - Muhammad Aliv Kusuma Putra; Irvina Nurrachmi; Irwan Effendi (Tropical Marine Enviromental Sciences, 2022)
Spirulina platensis is a marine microalga that has potential as a natural fish feed and is considered an absolute food supplement to combat malnutrition in some countries. Azolla microphylla is a water fern that has been cultivated, contains high protein, grows quickly and is widely found in tropical waters. This study analyzed the effect of liquid fertilizer of A.microphylla on population growth and chlorophyll content of S. platensis. A completely randomized design (CRD) was used and the treatments were A (3 mL/L), B (5 mL/L) and C (7 mL/L), D (negative control without liquid fertilizer) and E (positive control, addition of 1 ml/L Walne fertilizer). The measurement results showed that the water quality during the study was in good condition, the water temperature ranged from 28-29 C, pH (7-8) and salinity (25 - 26 ppt). The highest population density level of S. platensis (321,500 cells/mL) was recorded in treatment B. Then followed by treatment D (270,600 cells/mL), treatment C (260,000 cells/mL), treatment A (220,000 cells/mL) and treatment E (150,000 cells/mL). The highest chlorophyll content was found in treatment C of 0.362 g/L, treatment D (0.302 g/L), treatment A (0.182 g/L), treatment B (0.250 g/L), and treatment E (0.072 g/L).